Intro to quantum computing & BB84 key distribution protocol (Manning Publications Co., 2022)
Mariia Mykhailova, a Principal Software Engineer at Microsoft Quantum, introduces the quantum key distribution problem and describes the most famous quantum key distribution protocol - BB84 protocol, proposed by Charles Bennett and Gilles Brassard in 1984. She also talks about her liveProject covering the implementation of this protocol using Microsoft Quantum Development Kit.